2014
DOI: 10.1002/cplu.201300278
|View full text |Cite
|
Sign up to set email alerts
|

Assembly of TiO2‐on‐Cu2O Nanocubes with Narrow‐Band Cu2O‐Induced Visible‐Light‐Enhanced Photocatalytic Activity

Abstract: Newly designed TiO2‐on‐Cu2O nanocubes have been constructed as visible‐light‐driven photocatalysts with high efficiency by means of a facile self‐assembly approach at room temperature. In the resultant TiO2‐on‐Cu2O nanocubes, the TiO2 nanoparticles with a diameter of 6–8 nm show a well‐monodispersed distribution of the 200–300 nm‐sized Cu2O single‐crystal nanocubes, which can form sub‐monolayer, monolayer, and multilayer coverage through controlling the ratio of the two phases. In particular, the coupling of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…In addition to the semiconductor-cocatalyst and semiconductor-carbon heterojunctions, heterojunctions consisting of two different semiconductors have been effectively used to improve the photostability of semiconductors and boost their overall photocatalytic activity. Typically, the type II heterojunctions, such as Cu 2 O/TiO 2 and CdS/TiO 2 , and all-solid-state Z-scheme systems have been extensively and rationally designed to decrease photocorrosion of unstable Cu 2 O and CdS. Finally, preparation of protective overlayers, such as TiO 2 , SrTiO 3 , g-C 3 N 4 , Co–Pi, , CoO x , Al 2 O 3 , Ga 2 O 3 , and SiO 2 , on semiconductors can “passivate” or “catalyze” their surface to reduce charge recombination or enhance charge transfer, respectively, thus effectively boosting the overall photocatalytic activity .…”
Section: Fundamentals Of Heterogeneous Co2 Photoreductionmentioning
confidence: 99%
“…In addition to the semiconductor-cocatalyst and semiconductor-carbon heterojunctions, heterojunctions consisting of two different semiconductors have been effectively used to improve the photostability of semiconductors and boost their overall photocatalytic activity. Typically, the type II heterojunctions, such as Cu 2 O/TiO 2 and CdS/TiO 2 , and all-solid-state Z-scheme systems have been extensively and rationally designed to decrease photocorrosion of unstable Cu 2 O and CdS. Finally, preparation of protective overlayers, such as TiO 2 , SrTiO 3 , g-C 3 N 4 , Co–Pi, , CoO x , Al 2 O 3 , Ga 2 O 3 , and SiO 2 , on semiconductors can “passivate” or “catalyze” their surface to reduce charge recombination or enhance charge transfer, respectively, thus effectively boosting the overall photocatalytic activity .…”
Section: Fundamentals Of Heterogeneous Co2 Photoreductionmentioning
confidence: 99%
“…World energy demand is expected to increase at a rate of 2.2% per year from 2012 to 2035, with demand in buildings and industrial sectors accounting for 90% of this growth [1]. In order to mitigate climate change [2], both European [3] and UK [4] national policies suggest that efforts should be made to ensure sustainable development in future. One effective dispatch strategy of CES is formulated as a Mixed Integer Linear Programming (MILP) function to minimise the amount and price of energy absorbed from the grid.…”
Section: Introductionmentioning
confidence: 99%
“…From the studies reported, n-type TiO 2 coupling with p-type Cu 2 O exhibits good prospects for photocatalytic applications under visible light. For example, it was used in different applications such as the removal of organic and inorganic pollutants [20,[25][26][27][28], CO 2 reduction [29,30], H 2 evolution [14,[31][32][33], polyester textiles [34], as well as for antibacterial activity [35,36].…”
Section: Introductionmentioning
confidence: 99%